Effect of Different Slaughter Weights on Slaughter and Carcass Traits of Male Karayaka Lambs Reared under Intensive Production System - Yüksel Aksoy; Zafer Ulutaş (Turkish Journal of Agriculture: Food Science and Technology)
The present study was conducted to investigate the carcass traits of Karayaka lambs slaughtered at different slaughter weights (SWs) and to find out optimum SWs. Male Karayaka lambs with 20 kg live weight (n=30) constituted the animal material of the study. Lambs were randomly divided into five SW groups; 30 (GI; n=6), 35 (GII; n=6), 40 (GIII; n=6); 45 (GIV; n=6) and 50 (GV; n=6) kg. Lamb fattening feed (concentrate feed, ad libitum) and forage (lentil straw, 100g/lamb/day) were used as the feed material. Lambs were sent to slaughter at target SWs. Following the slaughter, non-carcass components, tailless hot and cold carcass weights were taken. Carcasses were separated into six sections as leg, foreleg, back, loin, neck and others. Physical dissection was performed to investigate carcass composition. Only the differences in carcass dressing and skin percentages of slaughter groups were not found to be significant. Increasing carcass fat percentages and decreasing carcass lean and bone percentages were observed with increasing SWs. Considering the consumer preferences, current findings revealed that Karayaka lambs should be sent to slaughter at weights between 30-35 kg. However, considering the red meat deficit of the country, current market conditions and producer preferences, the optimum SW for Karayaka lambs were recommended to be between 40-45 kg.